2014
DOI: 10.1161/hypertensionaha.113.02722
|View full text |Cite
|
Sign up to set email alerts
|

Altered Inflammatory Response Is Associated With an Impaired Autonomic Input to the Bone Marrow in the Spontaneously Hypertensive Rat

Abstract: Autonomic nervous system (ANS) dysfunction, exaggerated inflammation and impaired vascular repair are all hallmarks of hypertension. Considering the bone marrow (BM) is a major source of the inflammatory cells (ICs) and endothelial progenitor cells (EPCs), we hypothesized that impaired BM-ANS interaction contributes to dysfunctional BM activity in hypertension. In the SHR, we observed a >30% increase in BM and blood ICs (CD4.8+), and a >50% decrease in EPCs (CD90+.CD4.5.8-) compared to the normotensive Wistar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
125
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(145 citation statements)
references
References 25 publications
(31 reference statements)
7
125
1
1
Order By: Relevance
“…Recent studies have shown that increased arterial stiffness associated with aging is closely related to increased sympathetic nerve activity 36 and, consequently, exacerbation of the inflammatory process. 37 It is important to note that the chronic diseases most associated with increased PWV (diabetes, hypertension and obesity itself) have an underlying inflammatory component. Thus, the PWV measurement could represent the clinical sentinel monitoring the chronic inflammatory process in these conditions.…”
Section: Determinants Of Arterial Stiffnessmentioning
confidence: 99%
“…Recent studies have shown that increased arterial stiffness associated with aging is closely related to increased sympathetic nerve activity 36 and, consequently, exacerbation of the inflammatory process. 37 It is important to note that the chronic diseases most associated with increased PWV (diabetes, hypertension and obesity itself) have an underlying inflammatory component. Thus, the PWV measurement could represent the clinical sentinel monitoring the chronic inflammatory process in these conditions.…”
Section: Determinants Of Arterial Stiffnessmentioning
confidence: 99%
“…We have recently suggested a direct role for inflammatory BM cells in the pathophysiology of hypertension (HTN) in rodent models that present with this condition (13,24,35). More specifically, we observed a significant increase in BP in the normotensive Wistar-Kyoto (WKY) rat strain following a full ablation and reconstitution of their IS with BM cells derived from spontaneously hypertensive rats (SHRs) (24).…”
mentioning
confidence: 99%
“…Activation of the BM beta 1 and 2 adrenergic receptors, in particular, has been shown to modulate the levels of different immune cells in circulation, with inflammatory cells predominantly released during the highest activity period [i.e., night time in rodents and day time in humans (5, 9, 17, 18, 25)], an evolutionary mechanism developed to prime the system for warding off infection, should the need arise. On the other hand, the reciprocal action of an activated IS on the CNS has also been suggested, with significant evidence for the role of an exaggerated IS in diseases of the cardiovascular system (CVDs) as well as metabolic diseases such as diabetes and obesity (3,12,24,27).We have recently suggested a direct role for inflammatory BM cells in the pathophysiology of hypertension (HTN) in rodent models that present with this condition (13,24,35). More specifically, we observed a significant increase in BP in the normotensive Wistar-Kyoto (WKY) rat strain following a full ablation and reconstitution of their IS with BM cells derived from spontaneously hypertensive rats (SHRs) (24).…”
mentioning
confidence: 99%
See 2 more Smart Citations